(Smart CPS) An Internet-of-Things (IoT) based cyber manufacturing framework for the assembly of microdevices. Issue 4 (4th May 2019) - Cecil, J.; Albuhamood, Sadiq; Ramanathan, Parmesh; Gupta, Avinash
ABSTRACT: The emergence of Cyber-Physical Systems (CPS) based principles and technologies holds the potential to facilitate global collaboration in various fields of engineering. Micro Devices Assembly (MDA) is an emerging domain involving the assembly of micron-sized objects and devices. In this paper, a novel IoT based Cyber-Physical framework for MDA is discussed. The proposed IoT framework is the first of its kind for the process domain involving the assembly of micron-sized parts. Another innovation is the exploration of the feasibility next generation Software Defined Networking (SDN) principles to support distributed collaborations involving cyber and physical components within this framework. A unique information model-based monitoring approach is proposed to monitor and track the cyber-physical interactions. The advanced collaborative Cyber-Physical framework comprising of cyber and physical components linked using Next Generation Internet technologies has been developed to accomplish a targeted set of MDA life cycle activities which include assembly planning, path planning, Virtual Reality (VR) based assembly analysis, command generation and physical assembly. Genetic algorithm and modified Insertion algorithm-based methods have been proposed to support assembly planning activities. Advanced VR-based environments have been designed to support assembly analysis where plans can be proposed, compared and validated. The feasibility of the Cyber-Physical approach has been demonstrated by implementing an IoT Test Bed to assemble micro designs.